The Effect of Investor Sentiment on Betting Against Beta: A SEM Approach Towards Beta Anomaly - Abdollahi, Hooman; Ebrahimi, Seyed Babak; Tayebi, Hamed (International Journal of Economics and Financial Issues, 2017)
Beta anomaly is one of the greatest anomalies in finance literature as CAPM conveys a positive relationship between the beta of a stock and future returns; however, empirical studies do not document this proposition. Branded as betting against beta, this conundrum is known as a controversial subject. Drawing on literature the authors propose new multi-factor models to develop our understanding of betting against beta using investor sentiment as well as Structural Equation Modeling methodology to gauge the models in the presence of the top-down approach. Results indicate that investor sentiment provides a good explanation of the betting against beta. Limitation and future research directions are presented at the end of paper. Keywords: Behavioral finance, Investor sentiment, BAB factor JEL Classifications: G02, G10